(untitled) (Economics and region, 2023)
The article examines the peculiarities and trends of the development of medical tourism in Turkey in the context of the globalization of the medical space, as well as in the context of the implementation of this experience in Ukraine. The current state, and organizational aspects of the functioning of medical tourism in Turkey, as a promising direction of tourism in Ukraine, are analyzed. According to the Medical Tourism Index, Turkey is among the TOP-10 leaders in medical tourism [10]: 750,000 foreign patients choose local clinics every year. Ukraine has a well-developed base and potential for the development of medical tourism, but the problems that hinder it remain unresolved. The system of medical tourism needs to work, for which it is necessary to create an effective model of marketing policy in health care, improve the material base and introduce modern medical technologies, change the legislation, undergo international certifications, adjust the service, and raise the quality of services to a higher level.